THE IMPACT OF CHANGE MANAGEMENT ON THE QUALITY OF THE WORK ENVIRONMENT: A STUDY OF THE EMPLOYER-EMPLOYEE RELATIONSHIP OF SENIOR CUSTOMS SUPERVISORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study examines the impact of change management on the quality of the work environment by analysing the employer-employee relationship among senior customs supervisors working at Latgale customs checkpoints. The necessity to adapt personnel management approaches within the Customs Board is highlighted, taking into account the sustainable development goals of the institution. A quantitative survey was conducted involving 113 respondents, representing different socio-demographic groups. The analysis of the results revealed significant differences in the perception of work environment dimensions, with educational level showing the strongest influence. However, gender, marital status, family responsibilities, and management experience also showed variations that should not be overlooked when shaping change management strategies. The findings demonstrate that socio-demographic and professional profiles have a complex effect on employees’ satisfaction and perception of the working environment. Based on the results, recommendations are proposed to incorporate these factors systematically into personnel management practices, aiming to strengthen institutional efficiency and improve the well-being of customs employees.